Performance evaluation of an integrated cooling and power system combining supercritical CO2, gas turbine, absorption refrigeration, and organic rankine cycles for waste energy recuperating system - Bishal, Salim Sadman; Faysal, Dewan Fahim; Ehsan, M Monjurul; Salehin, Sayedus (Results in engineering, 2023)
This study proposes and explores a unique integrated cooling and power system in which waste heat from a gas turbine (GT) cycle is collected and used to generate electricity via a supercritical CO2 (sCO2) recompression Brayton cycle (sCO2RBC) and an organic Rankine cycle (ORC). An absorption refrigeration cycle (ARC) recovers waste heat from the sCO2RBC in order to provide a cooling impact. An energy analysis is carried out where mathematical modelling has been performed by a validated one-dimensional Python code. For working fluids e.g., air, combustion/exhaust gas, and NH3–H2O solution, property equations are used for obtaining the properties of respective state points. Impacts of different parameters are investigated on the total power output, net cooling effect and net energy utilization. The work emphasizes on modeling a novel integrated cooling and heating power system that utilizes the next generation sCO2 cycle, as well as other conceivable combinations, to effectively and reliably recover the waste heat. The analysis reveals that except for difference in the temperature in the hot side of the generator, all of the parameters increase resulting in an increase in net work done. The increase in temperature at inlet of GT, pressure ratio of the RBC, the decrease in GT pressure ratio, isentropic efficiency of GT, and lastly the temperature variation in the hot side of absorption refrigeration cycle generator affects the co-efficient of performance (COP) & energy utilization factor (EUF) of combined system. The EUF achieves a highest value of 49.09% and COP of 0.72. •An integrated cooling and power system is proposed for waste heat Recuperation•Cycles are Supercritical CO2, Gas Turbine, Refrigeration, and Organic Rankine•Detailed thermal analysis performed with a validated one-dimensional Python code•ParaMetric analysis performed to obtain Energy Utilization Factor (EUF)